An insurance mechanism for electricity reliability differentiation under deep decarbonization. (1st September 2022) - Billimoria, Farhad; Fele, Filiberto; Savelli, Iacopo; Morstyn, Thomas; McCulloch, Malcolm
Abstract: Securing an adequate supply of dispatchable resources is critical for keeping a power system reliable under high penetrations of variable generation. Strategic reserves have been used by a range of jurisdictions to procure investment in additional generation reserves given the missing money problem in energy only market designs. Given the growing flexibility and heterogeneity of load enabled by advancements in distributed resource and control technology, strategic reserve procurement needs to be able to reflect the different preferences of energy consumers. To address this challenge this paper develops an insurance risk mechanism for the procurement of strategic reserves that is adapted to a future with variable generation and flexible demand. The proposed design introduces a central insurance scheme with prudential requirements that align diverse consumer reliability preferences with the financial objectives of an insurer-of-last-resort. We illustrate the benefits of the scheme in (i) differentiating load by usage to enable better management of the system during times of extreme scarcity, (ii) incentivizing incremental investment in generation infrastructure that is aligned with consumer reliability preferences and (iii) improving overall reliability outcomes for consumers. Highlights: Differential reliability enabled by aligned financial insurance risk exposures. Incremental investment in generation aligned with consumer preferences. Improving overall reliability outcomes for consumers with affordable insurance premia. Demonstrated reliability improvements over energy-only market design.